Happiness - Harleman, Ann, 1945- (John Simmons short fiction award., 1994)
In Ann Harleman's remarkable debut collection, men and women of extraordinary passions look for and sometimes find the hidden heart of ordinary life. Testing themselves and each other, they search for ways to connect. "Understanding," says the troubled voyeur-narrator of "Imaginary Colors," "is the booby prize"; these characters go for experience. Reckless explorers of inner space, they try the limits of their lives. A gravely ill woman seeks forgiveness from her grown-up daughters for an adulterous past which she does not really regret.